Attitudes towards Euro Area Reforms: Evidence from a Randomized Survey Experiment - Mathias Dolls; Nils Wehrhöfer (Center for Economic Studies and ifo Institute (CESifo), 2018)
We present the first evidence on public attitudes towards two prominent euro area reform proposals (European Unemployment Benefit Scheme and Sovereign Insolvency Procedure) and assess potential impediments to their implementation by means of a randomized survey experiment in Germany. We find that there is a low willingness among German voters to accept fiscal risk-sharing through common unemployment insurance, while a sovereign insolvency procedure aimed at strengthening market discipline is supported by a majority of the electorate. Our randomized treatments confronting survey participants with potential adverse effects of the reforms lead to significant downward shifts in approval rates. Altruism, cosmopolitanism, political preferences and income are important predictors of support for the reform proposals. We also show that there is a striking contrast between the low level of support for transfers to other euro area member states and a broad acceptance of inner German transfers.
Keywords: H55; H24; J26; D14; 330; public attitudes; euro area reforms; European unemployment insurance; sovereign insolvency procedure